PCDH19-Related Epilepsy in Early Onset of Chinese Male Patient: Case Report and Literature Review - Yang, Xiao; Chen, Jing; Zheng, BiXia; Liu, Xianyu; Cao, Zixuan; Wang, Xiaoyu (Frontiers in Neurology, 2020)
Mutations in PCDH19 are associated with epilepsy, intellectual disability and behavioral disturbances, mostly related to females. The unique X-linked pattern of inheritance affects females predominantly, while usually is transmitted through asymptomatic males. Recently, new research has demonstrated that males with a mosaic pattern of inheritance could also be affected. As yet, PCDH19 mutations have been reported in hundreds of females; however, only 15 mosaic males were reported to exhibit epileptic seizures with the onset ranges between 6 to 31 months. These patients were usually reported to carry various mutations in the PCDH19. Here we describe a nonsense variant at the PCDH19 (c.498C>G; p.Y166*) in the Chinese male that exhibited early developmental delay and frequent seizures starting from the age of five months. We aim that this case report, focusing on studying clinical seizures, therapeutic approaches, and the patient’s prognosis, will contribute to the cumulative knowledge of this rare and complex genetic disorder.